DATA ANALYTICS FOR AUDIENCE PREFERENCES IN PHOTOGRAPHY - Kumar, Saurabh; Parmar, Yuvraj; Smitha K; Mahajan, Shriya; Gaur, Anushree; Walia, Anita; Barkade, Shrikant Shrimant (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Photography as a visual art form and effective medium of communication has experienced a major revolution in the digital era. As the social media platforms and visual content consumption have expanded rapidly, the need to comprehend the preferences of the audience has become the major matter of focus among photographers, brands, and creators of visual content. In this paper, the authors discuss the application of data analytics to analyse, interpret and forecast the audience behavior in the context of photographic content. The study combines the methods of quantitative, qualitative, and mixed methods to be based upon the existing literature that deals with the topics of engaging with visual media and making a creative decision based on the numbers. The social media analytics, surveys, and level of engagement are integrated in data collection, and to extract full insights, the analytical tools, Python, R, and Tableau are used. Analysis explores descriptive patterns of engagement, demographic and psychographic patterns of audience, and correlation of photographic styles and reactions of the viewer. Also, predictive modeling is employed to determine the arising preferences and future aesthetic trends in digital photography consumption. The results indicate the increased value of customized visual content, optimization techniques of gaining the interest of social media users, and the use of predictive analytics to forecast market changes.